Barriers to The Adoption of Modular Construction Technology In South Africa - Matoba, Mokete; Amoah, Christopher (CSID Journal of Infrastructure Development, 2025)
Construction, mining, and manufacturing are the most significant contributors to South Africa's GDP. While manufacturing and other industries utilise advanced technologies to enhance productivity, he construction industry continues to lag behind in technological adoption. This study examines the barriers that hinder the South African construction industry from leveraging the benefits of modular construction technologies (MCT). The study employed a quantitative research method, using closed-ended questions to collect data. The questionnaires were emailed to South African construction industry professionals selected through a combination of purposive and convenience sampling. A total of 98 questionnaires were distributed, of which 46 were returned. However, only 41 were deemed valid for analysis, and five incomplete responses were excluded. The data obtained were analysed using descriptive statistics. The study highlighted that modular construction technology is not yet widely encouraged in the South African construction industry. This indicating a need for increased awareness and education regarding this technology. Some barriers to the adoption of modular construction include a lack of knowledge among construction stakeholders, aesthetic concerns, difficulties in making changes, limited contractor expertise in modular construction, and transportation constraints. The lack of adoption of modular construction technology in South Africa deprives the industry of the benefits associated with this construction method, such as improved production efficiency, which have been realised by other sectors that have successfully adopted advanced technologies in their production processes. Therefore, construction industry stakeholders should implement targeted measures to address adoption barriers. The study provides a clearer and more comprehensive understanding of the perceptions of industry stakeholders regarding the factors that hinder the adoption of modular construction technology.